Features of Structural and Functional Model of Students' Professional Mobility Formation - Vladimir A. Mishchenko; Natalya V. Ðšharina; Anna V. Molokova; Irina L. Belenok; Aleksandr A. Nikitin; Olga A. Nikitina; Valery F. Glushkov; Nadezhda V. Silkina (International Review of Management and Marketing, 2016)
The relevance of the study to these problems reasoned by the fact that in economic crisis and social dynamism times the problem of professional self-determination of the individuals considered from a different point of view, because people can repeatedly change their occupational status, qualifications and enterprise team during their whole lives. In this regard, this article is dedicated tithe development of structural-functional model of students' professional mobility formation in modern conditions. The article presents the features of the regional structural and functional model of students' professional mobility formation developed by the authors, comprising the following relationship of its components: the regional social order for human resources' training, target, content-procedural, technological, monitoring and assessment-productive ones. This models based on social partnership and coordination of students' vocational training with an innovative educational environment of the region. Pedagogical conditions of students' professional mobility formation are proposed, the practical implementation of which in a particular individual institution of higher educationist related to the need to take into account regional factors: the possibilities of the institutions, the availability of companies and organizations in which the students can have practice, geographical location and regional affiliation of the city where the high school is located.